Mo3VOx catalyst in biomass conversion: A review in structural evolution and reaction pathways - Bagheri, S.; Julkapli, N.M. (Elsevier, 2017)
Mo3VOx heterogeneous catalyst is among the complex metal oxides that have piqued recent interest due to its superior ýcatalytic properties. Its synthesis via sol gel or hydrothermal methods focused on the production of pentagonal polyoxomolybdate unit in the reaction precursor assembles with other V and Mo ions to form crystalline MoV oxides with pentagonal, hexagonal, and heptagonal units in either trigonal or orthorhombic phases. Moreover, the orthorhombic structure of Mo3VOx catalyst exhibited particularly high catalytic activity for selective oxidation of ethane, propane, and acrolein, whereby the reaction can take place not only in the mouth of heptagonal channels, but also in the entirety of the Mo3VO4 channel. Indeed, the Vanadyl groups with vanadium at the crystallographic positions are accountable for C–H activation of propane in the rate determining abstraction of the first H2 atoms. The molybdenum surface enrichment is detrimental with respect to the selectivity of the reaction. With that advantage, Mo3VOx has been applied as a catalyst for the acrolein oxidation to acrylic acid, selective oxidative activation of alkanes, ammoxidation of propane to acrylonitrile, or to acrylic acid, oxidation of n-butane to maleic acid or anhydride, oxidative of dehydrogenation of ethane to ethylene, or oxidation of ethane to acetic acid and partial oxidation of alcohols/aromatic hydrocarbon. Abundant metal components, such as Fe, W, Cu, Nb, and Te, have been used with the intention of optimizing the structure and catalytic performance, elucidating structural peculiarities, and improving catalytic performance.